2010
DOI: 10.1057/rlp.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ ideal eating out experience as it refers to restaurant style: A case study

Abstract: and Leisure. He is the faculty of Business and Law, Edith Cowan University. His research interests include business-related areas of concern of small and medium enterprises, urban (for example, hospitality) and rural (for example, wineries), as well as wine consumer and winery visitor behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…The restaurant industry is a unique and complex business, needing expertise in many areas, from production to service orientation (Wyckoff, 2001). Restaurateurs need to be concerned with both product quality and service quality (Alonso & O'Neill, 2010;Bojanic & Rosen, 1994). In the service industry, service quality and customers' intentions to return are of paramount importance for organizational success.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
“…The restaurant industry is a unique and complex business, needing expertise in many areas, from production to service orientation (Wyckoff, 2001). Restaurateurs need to be concerned with both product quality and service quality (Alonso & O'Neill, 2010;Bojanic & Rosen, 1994). In the service industry, service quality and customers' intentions to return are of paramount importance for organizational success.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
“…However, Soriano (2003) claimed that offering good food and quality service were not enough to attract consumers and that restaurants should provide meals with good value in a favorable ambience. Previous studies (Alonso and O'Neill, 2010;Barta, 2008;Cullen, 2004) showed that attractive décor and atmosphere also influenced consumers' restaurant choices. Alonso and O'Neill (2010) found that the restaurant environment affected consumers' choice of restaurant including comfort and cleanliness, which also influenced consumers' perception of food safety at restaurants.…”
Section: Factors Influencing Healthy Eating Behaviors At Restaurantsmentioning
confidence: 98%
“…Consumer decisions when buying in some places tend to be due to the atmosphere compared to the product / food offered, harmony between tangible and intangible can be achieved through physical appearance such as food and wine combined with restaurant interiors (physical structure and artifacts). The atmosphere which consists of temperature, lighting, aroma, and sound directly contribute to creating a dining experience (Alonso and O'Neill, 2010).…”
Section: The Role Of Paper Tole As Well As Interior Space Filling Accmentioning
confidence: 99%